Analysis of the Corn Dehydration Process (Zea Mays) in a Fluidized Bed Dryer - Fernandez Ayma, Alfredo (2019)
The present work was developed in the Department of Apurímac, Province of Abancay, in the Unitary Operations Labora-tory of the Professional Academic School of Agroindustrial Engineering. The main objective of the research was to determi-ne which mechanical elements influence the drying time. The problem in the dryers is the consumption of energy therefore the fans that drive the air are incorporated to reduce drying time and also increases the turbulence of the air but the expen-diture of the electric power in higher, the research was developed to optimize the drying time in a fluidized bed dryer, JAR-CON, Model SLFT-60-240X, the method used for the determination of humidity is AOAC (2005) and the design applied was the complete random block (22 * 3) to evaluate the variables of answers, manipulating two factors such as the fan and ex-tractor. The most important conclusions were, the shortest drying time resulted with the auxiliary equipment of the fan and extractor reaching a temperature of 36.9 oC with an average time of 14.7 hours, with the equation exponentially with a co-rrelation coefficient of R2 of 0.9488 and secondly is when the fan operates at a temperature of 35.1 oC with a time of 16.8 hours with R2 of 0.9388